Tendu: An Underutilized Wild Fruit - Kumar, Ajay; Jangid, Rakesh; Gupta, A K; Anumala, Nikhila Vaagdevi; Kharga, Sudeshna (Indian Horticulture, 2024)
Diospyrus melanoxylon Roxb., is commonly known as tendu, belonging to the family Ebenaceae which is endemic to the Indian subcontinent. It is an underutilized edible fruit and is the most important fruit of Central India (Madhya Pradesh, Chhattisgarh, Jharkhand, Odisha and some parts of Uttar Pradesh) and forest regions. It is evergreen or deciduous in nature depending upon its habitat. The paper discusses the general properties of Tendu and its importance.